2006
DOI: 10.1007/s11104-006-0045-9
|View full text |Cite
|
Sign up to set email alerts
|

Water relations and gas exchange in olive trees under regulated deficit irrigation and partial rootzone drying

Abstract: It is widely believed that partial root drying (PRD) reduces water losses by transpiration without affecting yield. However, experimental work carried out to date does not always support this hypothesis. In many cases a PRD treatment has been compared to a full irrigated treatment, so doubt remains on whether the observed benefits correspond to the switching of irrigation or just to PRD being a deficit irrigation treatment. In addition, not always a PRD treatment has been found advantageous as compared to a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(94 citation statements)
references
References 43 publications
8
79
0
3
Order By: Relevance
“…Similarly, experiments with RDI have been successful in citrus (Domingo et al 1996;González-Altozano and Castel, 1999;Goldhamer and Salinas, 2000). Similar results were reported for almond , apple (Ebel et al, 1995), apricot (Ruiz-Sánchez et al, 2000), pear (Mitchell et al, 1989), pistachio (Goldhamer and Beede, 2004), wine grape vines (Bravdo and Naor, 1996;McCarthy et al, 2002), and olive (Moriana et al, 2003;Fernández et al, 2006). Accordingly, Fereres and Soriano (2007) published a comprehensive review on the use of deficit irrigation techniques to reduce water use in agriculture.…”
Section: Wwwintechopencomsupporting
confidence: 52%
“…Similarly, experiments with RDI have been successful in citrus (Domingo et al 1996;González-Altozano and Castel, 1999;Goldhamer and Salinas, 2000). Similar results were reported for almond , apple (Ebel et al, 1995), apricot (Ruiz-Sánchez et al, 2000), pear (Mitchell et al, 1989), pistachio (Goldhamer and Beede, 2004), wine grape vines (Bravdo and Naor, 1996;McCarthy et al, 2002), and olive (Moriana et al, 2003;Fernández et al, 2006). Accordingly, Fereres and Soriano (2007) published a comprehensive review on the use of deficit irrigation techniques to reduce water use in agriculture.…”
Section: Wwwintechopencomsupporting
confidence: 52%
“…However, in some fruit species, PRD has given similar results to those obtained with RDI, with no clear advantage of the former when the volumes of water applied in both methods were the same (Egea et al, 2010). Roots left in drying soil under localized irrigation system might be responsible for the reduction on transpiration and there is no need to alternate irrigation for achieving this effect (Fernández et al, 2006).…”
Section: Partial Rootzone Dryingmentioning
confidence: 79%
“…Although there are a handful of studies in which negative results have been reported after applying PRD (Gu et al 2004;O'Connell & Goodwin 2004Neuhaus et al 2007), there are a greater number of studies that demonstrate successful application of the technique to grapes (Dry et al 1996;Loveys et al 1998;Stoll et al 2000;Chalmers et al 2004) and many other horticultural crops including apple (Leib et al 2006), pear (Kang et al 2002), mango (Spreer et al 2009), olive (Fernandez et al 2006), tomato (Tahi et al 2007) and raspberry (Grant et al 2004).…”
Section: Introductionmentioning
confidence: 99%